Investigation of insulin promoter factor 1 gene C18R and R197H variants association with type 2 diabetes mellitus in Bangladeshi population - Eusufzai, Tasnin Khan (Brac University, 2019)
This thesis report is submitted in partial fulfilment of the requirement for the degree of Master of Science in Biotechnology, 2019.